(untitled) (Cadernos de Sociomuseologia, 2016)
This paper seeks to increase the understanding how of museum can contribute to an interdisciplinary knowledge construction. The article aims to show how interdisciplinarity can be exercised, as well as you can now justify the construction of an interdisciplinary attitude to knowledge. The notions of Phenomenology and Contemporary Art underlie research. The interdisciplinarity, to emphasize the importance of inter and partnerships, and also highlights its five guiding concepts (humbleness, respect, coherence, expectation, and detachment), it is an attitude that can facilitate the educational and institutional intentions of the museum in an attempt to share their cultural and artistic heritage with the public. The interdisciplinarity in the category of state action can achieve in the museum, institutional demands and educational projects trampled a phenomenological view, which means to understand it as being creative, collective and questioning. This man, who question the sense of things, when faced with the contemporary art in the museum, you can build knowledge articulating their experiences to the different areas of knowledge that permeate the plastic arts, adding to the conceptual discourse aspects of reality. When considering the reality, the museum plays an important social role: generate motivations and reflections that continue beyond the museum. Keywords: Education; interdisciplinarity; phenomenology; museums; contemporary art